ANALYSIS OF FACTORS AFFECTING MATHEMATICAL RESILIENCE OF MTS ATS TSABAT MAKASSAR (International Conference on Social and Islamic Studies, 2022)
The purpose of this study was (1) to describe the mathematical resilience of students at MTs Ats-Tsabat Makassar. (2) to determine the factors that affect the mathematical resilience of students at MTs Ats-Tsabat Makassar. This research is a type of mixed method research, namely research that uses two methods, namely quantitative methods and qualitative methods, in order to obtain comprehensive, valid, reliable, and objective data. The research design used is a sequential explanatory design. This design is applied by collecting and analyzing quantitative data in the first stage, followed by the collection and analysis of qualitative data in the second stage which is built on the initial quantitative results. The sample used in this study was 44 students of MTs Ats-Tsabat Makassar for quantitative data, and 6 research subjects were selected based on quantitative analysis to be used as sources of qualitative data. The instrument used is a mathematical resilience questionnaire for quantitative data and interview guidelines as a tool for researchers, as the main instrument in collecting qualitative data. The questionnaire used has gone through validation tests from experts and instrument testing which includes validity and reliability tests. The results showed that: 1) The description of the mathematical resilience of MTs Ats-Tsabat Makassar students, namely the average was in the medium category with a percentage of 50%. 2) The factors that influence the mathematical resilience of MTs Ats Tsabat students based on the source of resilience I Have which means external support, it was found that family support factors and peer assistance factors were the determinants of increasing students' mathematical resilience. Then from the second source of resilience, namely I Am in the form of internal support, it was found that those that affect mathematical resilience are the interest factor, the independence factor and the religiosity factor. Then from the I Can source which comes from social and intrapersonal interactions, it is found that the communication ability factor and the emotional management factor can affect mathematical resilience.